Accreditation and the state of North Carolina: The revitalization of national standards - Vogel, Ronald E. (American journal of criminal justice, 1988)
From the mid to late 70s, the Academy of Criminal Justice Sciences (ACJS) developed a process for accrediting post-secondary criminal justice education programs. The academy gave form to the program by developing guidelines and a complex organizational network. However, the program did not reach fruition for a variety of economic and political reasons and it is doubtful that the Academy will attempt to resurrect the program soon. Even though the accreditation movement was abandoned on the national level, the North Carolina Association of Criminal Justice Educators (NCACJE) decided to implement the program and stepped into a very lengthy and political process.